A (in)convencionalidade das regras de contribuição sindical depois da reforma trabalhista à luz do princípio da liberdade sindical no sistema da Organização Internacional do Trabalho - Rodrigo Bilieri de Almeida (2024)
This piece of work studies the new legal norms of the annual union contribution promoted by the “Labour Reform” (Law No. 13,467 of 2017), in a legislative amendment to articles 578, 579, 582, 583, 587 and 602 of the Consolidation of Labour Laws (CLT) from Brazil. It is questioned the material compatibility of these legal provisions with the principle of freedom of association in its treatment by International Labour Organization’s (ILO) legal system of protection. The problem is delimited into three specific dimensions of the principle of freedom of association: the freedom of affiliation, the unions’ right to self-regulation and the unions’ freedom of administration. The main objective is to exercise the conventionality control, taking a position on the (un)conventionality of the aforementioned provisions of Law No. 13,467 of 2017 in relation to these selected matters of freedom of association. To this end, firstly, a study is conducted on the domestic norms of legal union contributions and the critical positions by national jurisprudence and national doctrine, before and after the Labour Reform. Afterwards, the international norms and other instruments regarding the dimensions of freedom of association are discussed. Finally, the conventionality control theory is analyzed and the intended conventionality sense is made. The result is that articles 578, 579, 582, 583, 587 and 602 of CLT in the text of Law No. 13,467 of 2017 are conventional regarding the freedom of affiliation, but they denote points of unconventionality in relation to the unions’ right to self-regulation and unions’ freedom of administration. The research also comes to the conclusion that the Labour Reform maintained unconventionalities that were already present in Brazilian regulation of union contributions before the legislative amendment. Furthermore, the national legal norms under scrutiny are not materially compatible with a series of international principles applicable to International Labour Law. Regarding the bibliographical references, it was substantially examined some doctrines of Brazilian Labour Law, International Law, International Labour Law and International Human Rights Law. Legal documents were consulted such as Law No. 13,467 of 2017, CLT, the ILO Constitution, the Philadelphia Declaration, the ILO Declaration on Fundamental Principles and Rights at Work, the Vienna Convention on the Law of Treaties, ILO Conventions and international human rights treaties. Legal documents (decisions of Committee on Freedom of Association) and soft law documents from ILO were also searched. The research is qualitative, basic, explanatory and bibliographic.